The development of a bridge network lifecycle prediction model for the Irish network - Reale, Tara M. (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2013)
The main aim of this thesis was the development of a bridge network condition prediction tool for the Irish network. This has been carried out with the intention of enabling the developed module to be incorporated into both new and existing BMS (Bridge Management Systems). EIRSPAN, the Irish BMS, will serve to provide the application data for the module, and since both EIRSPAN and the majority of BMS in existence worldwide, utilize a discrete condition state system to rank the structural health of their bridge stock, the research has focused on the application of Markov chain models in prediction systems - due to the ease with which the distinct condition states assigned to bridges during the visual inspection process lend themselves to the predefined states of condition needed for a Markov chain.
Keywords: Civil and Structural Engineering, Ph.D.; Ph.D. Trinity College Dublin